Pengungkapan Tanggung Jawab Sosial Perusahaan dan Tata Kelola Perusahaan yang Baik Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening - Dewi, Anastasya Vivian Risna; Diana, Nur; Fakhriyyah, Dewi Diah (Universitas Islam Malang, 2024)
This research aims to analyze and explain the relationship between Corporate Social Responsibility and Good Corporate Governance on company value with profitability as an intervening variable. The population of this research is banking companies listed on the Indonesia Stock Exchange in 2019-2023. The sampling technique used purposive sampling and a sample of 15 banking companies was obtained. The data analysis method in this research is quantitative data analysis using SmartPLS with hypothesis testing using the bootstrapping resampling method. The research results show that the Corporate Social Responsibility variable has no effect on company value, Good Corporate Governance has an effect on company value, Corporate Social Responsibility and Good Corporate Governance have no effect on profitability, profitability has an effect on company value, and profitability cannot mediate Corporate Social Responsibility and Good Corporate Governance.Keywords: Corporate social responsibility, good corporate governance, profitability, company value.